Research Interrupted: Improving Inuit Food Security Through Arctic Community-Based Research During the COVID-19 Pandemic - Mathieu, Kim (Université d'Ottawa / University of Ottawa, 2021)
This thesis addresses food security and road development in Tuktoyaktuk (population 995), a primarily Inuvialuit (Indigenous, Inuit) community in the western Canadian Arctic. Initially, I had hoped to conduct interviews in Tuktoyaktuk to better understand how the new Inuvik-to-Tuktoyaktuk Highway (ITH), opened in 2017 (the first highway to the Arctic Ocean) had affected food security in Tuktoyaktuk. This plan was interrupted. // INTERRUPTION \\ --THIS THESIS HAS BEEN INTERRUPTED \\ What do we do when our plans are forced to change? How do we react, adapt, and overcome these changes? How do we reflect on such interruptions? These questions are the underlying essence of this thesis and they reflect my experience of engaging in Arctic community-based research during the COVID-19 pandemic. This thesis presents two articles that are a result of many interruptions. The first (1) is an econometric evaluation of the cost of food before and after the opening of the ITH and the subsequent rescission of the Nutrition North Canada federal food subsidy program to the now road-accessible community of Tuktoyaktuk. The results suggest a significant increase in market basket prices which can be attributed to the opening of the highway and the subsidy loss (+CAD$44, SE = 16.77, p = 0.02). This research is the first to document the impacts of highway development on food prices in Arctic Indigenous communities. The second (2) is a co-authored methods piece about friendship, reciprocity, and reconciliation between two young women; a 17 year old Inuvialuit journalist and myself, a 25 year old Québécoise Master’s student, navigating research for the first time and during the pandemic. In the process, we reflect on what reconciliation means to us and provide recommendations for Arctic community-based research in a post-pandemic world. // BREAK. BREAK. THIS THESIS IS AN INTERRUPTION \\ In form and content, this thesis offers a reflection on the process of conducting and writing about research, juxtaposing qualitative (at times creative) and quantitative methods under a community-based research framework for working with Inuit.
Keywords: Food Security; Road Development; Arctic; Inuit; Community-Based Research; COVID-19; Pandemic